Chaetotaxy of tergits in the Archaeognatha (Insecta) and its taxonomic significance - Sturm, H.; Messner, B. (1995)
Owner: mattbowserAdded to JabRef: 2012.04.05
Keywords: Archaeognatha; chaetotaxy

Pedetontus gershneri, a new species of Machilidae from the interior highlands of North America (Insecta: Microcoryphia) - Allen, Robert T. (Entomological News, 1995)
Pedetontus gershneri, a new species of Microcoryphia, is described from Magazine Mountain, Logan County, Arkansas. The new species was found in leaf litter in dense deciduous forest. The presence of 2 pairs of exsertile vesicles on urosternites Il-V indicates a close relationship with Pedetontus species in western North America. Labial and maxillary palpi characters distinguish P. gershneri from its western relatives. Machiloides banksi, recorded for the first time from Arkansas, is found in more xeric habitats under rocks on the south facing slope of the mountain.
Owner: mattbowserAdded to JabRef: 2008.10.29
Keywords: Machiloides banksi; Pedetontus gershneri

On the systematics and phylogeny of the subfamily Petrobiinae (Thysanura, Machilidae) - Kaplin, V. G. (Zoologicheskii Zhurnal, 1995)
Owner: mattbowserAdded to JabRef: 2012.04.23